Investigating the causes of time budget overruns or delays during internal audit assignments: a case of OK Zimbabwe Limited - Mashanda, Sharai A. (Midlands State University, 2017)
The purpose of the research was to investigate the causes of time budget overruns during internal audit assignments at OK Zimbabwe Limited. Findings from literature review and data collected from the company indicated that time budget overruns where was as a result of circumstances from both the auditor and the client. The researcher used descriptive (qualitative) research methods in which census sampling method was used. A response rate of 87% percent was obtained and findings from questionnaires, interviews and secondary sources indicated that the auditor was more responsible for time budget overruns than the client which was in agreement with other scholars from literature review.